Innovation Efficiency of High-Tech SMEs Listed in China: Its Measurement and Antecedents - Lixia Liu; Yaming Hou; Xueli Zhan; Zongxian Wang (Discrete Dynamics in Nature and Society)
Innovation efficiency is an important index to measure the innovation performance of high-tech enterprises. Numerous researches have been conducted on innovation efficiency at national, regional, and sectoral levels, while there are comparatively few studies on the innovation efficiency of high-tech small- and medium-sized enterprises (SMEs) from a micro perspective. Therefore, innovation efficiency of 251 high-tech SMEs listed in China from 2012 to 2015 is measured with the super-SBM model in this paper. The results suggest that the overall innovation efficiency is low but shows an upward trend. In addition, the antecedents of innovation efficiency are explored using the panel regression model and the conclusions are as follows: (1) government subsidies, ownership concentration, and market competition deter enterprise innovation efficiency, and the impact of ownership concentration is found to be the most significant; (2) firm size and asset-liability ratio bear positively on enterprise innovation efficiency, with the effect of asset-liability ratio being greater; (3) firm age has significantly positive effects on scale efficiency but not on innovation efficiency and pure technical efficiency.